Air supply system transient model for proton exchange membrane fuel cell - Mahmoud Idres, Moumen Mohammed; Kafafy, Raed; Faris, Waleed Fekry (2011)
Proton exchange membrane (PEM) fuel cells are considered one of the best potential alternative power sources. It has both high efficiency and high power density. The air supply system dictates the performance of the fuel cell. It is responsible for supplying the correct amount of mass flow rate which is essential for ensuring efficient reaction of hydrogen and controlling the pressure inside the cathode. Pressure has a direct effect on the water balance characteristics and efficiency. In this work, a dynamic model for the air delivery system, including compressor and supply manifold, is developed. The model can capture both flow and inertia dynamics of the compressor. The model is tested by simulating the transient performance of the air supply system for a transportation-size fuel cell. A feedforward control method based on the compressor map is developed. Resuts shows the success of the model in predicting the transient behavior of the air supply system. The model can be used to implement and test different control strategies.